Strategi Komunikasi Public Relation PPTN 4 Regional II Dalam Menjalankan Program Gerakan Cinta Produk PTPN - Nazlia, Tatia; Nasution, Nurhasanah (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
The importance of a brand in the development of product or service businesses is evident from the high consumer desire to use goods or services with well-known brands. A widely recognized brand is often associated with quality, trust, and certain values, which encourage consumers to choose it over other products or services. Based on the researcher’s observations, the problem that occurs is the high market competition in product sales. Therefore, with the "Love PTPN Products" movement program, it is expected that more people will get to know and choose PTPN products. The aim of this research is to understand the public relations communication strategy of PTPN 4 Regional II in carrying out the "Love PTPN Products" movement program. The theory used in this research is the theory of internal and external communication. The method used in this research is descriptive qualitative. The techniques used to collect data include interviews, observations, and documentation conducted by the author at the research location. The data analysis techniques performed include data collection, data reduction, data presentation, and drawing conclusions. The researcher conducted interviews with two informants: the head of the sub-division and the public relations secretary of PTPN 4 Regional II. Based on the observations made by the researcher, the communication carried out by the public relations team of PTPN 4 Regional II used internal communication techniques by providing product testimonials to employees, followed by requiring employees to buy and use the company’s products. Additionally, the company also uses its own products to meet office facilities and equipment needs. In external communication, the company collaborates with various institutions and stakeholders, providing testimonials to each stakeholder as a form of product introduction. Another strategy is that the company always attends various events to introduce products and also utilizes social media to promote the products.